Estrutura de concorrência do setor bancário brasileiro entre 2009 e 2014: uma análise das economias de grandeza - Oliveira, Tiago Antonio de (2016)
This dissertation examines how the Brazilian banking system concentration process has shaped this industry competitive conditions and structure trying to identify whether the sector optimizes efficiency based on relevant literature. Firstly, the development of the banking sector is presented through a historical overview focused on two key events: the wholesale bank law of 1988, as well as, the financial stability reached by 1994. Secondly, the theoretical reference is presented as to fundament this academic debate. Quantitative data from Brazilian banking sector from September 2009 to December 2014 is presented and analyzed through concentration indicators as to measure the market concentration degree, the results suggests a highly concentrated market. Lastly, an econometric analysis of panel data estimates a regression used on the hypothesis test inferring the market structure with the Panzr-Rosse methodology. Results suggest that Brazilian banking sector is characterized as a monopolistic competition